Kajian Mutu Bata Beton Untuk Meningkatkan Mutu Produksi Dengan Menambah Admixture - Suwanto, Bodja (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2012)
Concrete blocks produced by local company in Banyumanik region at Pedalangan area are unable to reach its maximum compressive strength, compare to other company production in Semarang city. Testing its concrete block from UD DIPO company in Durian street, resulting of compressive strength on age of concrete 14 days, ?tk = 121.325 kg/ cm2, 21 days ?tk = 131.175 kg/ cm2, and 28 days ?tk = 150.625 kg/ cm2. So if it?s used for street pavement, its cannot handle heavy weight automobile, To increase compressive strength is with improving the quality of mixture material, such as sand, cement, fly ash, and the mixture must be added by WFA as much as 0.02 part, so the mixture of concrete block can be describe = 1 part of cement + 6 part of sand + 0.25 part fly ash + 0.02 part WFA and water added per use. After the concrete block being cast on a dice. then tested its compressive strength on 14 days old, its compressive strength became ?tk = 133.15 kg/ cm2, on the 21 day old it?s the compressive strength became ?tk = 199.525 kg/ cm2, and on the 28 days ?tk = 214.025 kg/ cm2. The result it the compressive strength reach + 40 %